Використання функцій попиту для збалансування розвитку продовольчих ринків - Федулова, І. В.; Мостенська, Т. Л. (Видавництво Львівської політехніки, 2015)
Досліджено попит на основні продукти харчування за допомогою функцій попиту від доходу і ціни. За допомогою виявлених функцій, обчислених на їх основі коефіцієнтів еластичності й основних індикаторів продовольчої безпеки можна аналізувати перспективи розвитку окремих галузей харчової промисловості, пріоритетність їх розвитку для забезпечення населення повноцінним збалансованим харчуванням. The article explores the demand for basic food products by means of functional relations between the demand, income and price. The objective function of food production shall be based on three main factors: physiological need in food, effective demand of population and commodity supply of manufacturers. The level and structure of food consumption indicate the level of stability and quality of life of the population. However, in conditions of commodity production and market the ability to meet the need for food products is limited by purchasing power of consumers. It is characterized by the amount of money that consumers can spend on the purchase of food. The price of a product can be viewed in two ways: from the point of view of consumers and in terms of entrepreneurs who produce and sell finished products. For consumers, price means opportunity to meet their needs in one way or another. One of the parameters of food security is the indicator of the proportion of expenditure on food in total household expenditures; it should not exceed 60 %. This value is a critical limit for the use of aggregate income of households. In 2013 this figure in Ukraine amounted to 50.1 %, indicating that people are near the poverty line, when more than half of total income is spent on food. Expenses of consumers on food have been growing because of three factors: growth of population and food intake; increase of food prices; consumers giving preference to more expensive products and marketing services. This study investigates the dependence between the expenditure proportion on food in total household expenditures in Ukraine and average wages of employees. The analysis of regression functions of dependencies of the average consumption of basic foodstuffs per capita from the average monthly wage of employees allowed to determine the direction, closeness and elasticity of these dependencies. Also the average chain elasticity coefficients of the price were investigated. Their values are not always negative, though the market is unsaturated not for all food groups. The prospects of development of individual sectors of food industry and the priority of their development for providing population with complete balanced diet can be analyzed using the identified functions, elasticity coefficients calculated on the basis of these functions and key indicators of food security.
Using demand functions for balancing food markets
Keywords: функції попиту; ціна; доход; еластичність попиту; продовольча безпека; demand function; price; income; elasticity of demand; food security